2019
DOI: 10.1108/k-02-2018-0078
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the high-tech industry with a multivariable grey forecasting model based on fractional order accumulation

Abstract: Purpose High-tech industries play an important role in promoting economic and social development. The purpose of this paper is to accurately predict and analyze the output value of high-tech products in Guangdong Province, China, by using a multivariable grey model. Design/methodology/approach Based on the principle of fractional order accumulation, this study proposes a multivariable grey prediction model. To further enhance the prediction ability and accuracy of the model, an optimized model is established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Proof. Since s r (j) keeps continduous over [i − 1, i], there exist the maximum value D and minimum value d for s r (j) over [i − 1, i], which makes d ≤ s r (j) ≤ D hold true; then, we have φd ≤ φs r (i) ≤ φD, (12) which is also…”
Section: Theorem 1 If S R (J) Is Continuous Over Given Intervalmentioning
confidence: 99%
See 1 more Smart Citation
“…Proof. Since s r (j) keeps continduous over [i − 1, i], there exist the maximum value D and minimum value d for s r (j) over [i − 1, i], which makes d ≤ s r (j) ≤ D hold true; then, we have φd ≤ φs r (i) ≤ φD, (12) which is also…”
Section: Theorem 1 If S R (J) Is Continuous Over Given Intervalmentioning
confidence: 99%
“…As previous literature revealed, for the ability to analyse and process data sequences, grey-based models have been broadly applied among diverse disciplines because of their excellent implementation on small-scale sample modeling, such as natural gas consumption [2][3][4], electric power supply and demand [5][6][7][8], renewable energy [9,10], industry [11,12], and medicine [13,14]. Although grey-based models have their own advantages, there still exist some shortcomings.…”
Section: Introductionmentioning
confidence: 99%
“…Grey prediction models play an important role in the grey system theory, which was pioneered by Deng [4]. At present, grey prediction models have been widely used in various fields of society due to their high prediction accuracy and the advantages of small sample modeling [5][6][7][8][9][10][11][12]. Depending on the number of variables required for modeling, grey prediction models can be divided into univariate grey prediction models and multivariable grey prediction models.…”
Section: Introductionmentioning
confidence: 99%
“…At present, scholars mainly focus on the improvement of the GM (1, 1) model, but there are few studies on the improvement of the GM (1, N) model. To fill this gap, Zeng et al established a new optimized grey prediction model and confirmed the feasibility and effectiveness of the model through examples [12]; in order to increase the adaptability of the multivariable grey prediction model, Wang established a multivariable grey prediction model with time power terms [13]; Xie et al established a discrete multivariate grey prediction model [14]; in order to further improve the adaptability of the discrete multivariable grey prediction model, Ding et al proposed a discrete multivariable grey prediction model with time power terms [15]; Considering that the discrete multivariable grey model has the problem of low model accuracy, Ding et al proposed a multivariate discrete grey prediction model with time delay effect [16]; Ma et al established a new multivariable grey prediction model with fractional order accumulation [17] and so on. ese improvements all further improved the accuracy of the multivariable grey prediction model and expanded the grey system theory.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the prediction accuracy of limited data with nonexponential growth trends, many scholars derived more models from traditional GM (1,1), such as the grey Verhulst model [11,12], grey Bernoulli model [13,14], and fractionalorder accumulation grey model (FGM) [15]. Since the fractional-order accumulation grey model solves the problem that the GM (1, 1) model cannot be used to predict the data that do not follow the grey exponential law completely accurately, it has attracted researchers' attention widely, such as Liu et al [16], Zeng [17], Wu et al [18], and Liu et al [19].…”
Section: Introductionmentioning
confidence: 99%